Comparison of two different orientations of advanced tight rope implant for distal radioulnar joint instability in same patient - efficacy, recovery and range of motion - Krishnan, Somasundar; Nagarajan, Anitha (International Journal of Research in Orthopaedics, 2026)
The distal radioulnar joint (DRUJ) is the wrist joint that allows rotation of forearm. It involves two bones-The Ulna and the Radius. The distal radioulnar joint is stabilised by ligaments, muscles and bones. The wrist or the forearm joint allows 180 degrees of pronation and supination of forearm by 4 components namely the Radio capitellar joint, the proximal radioulnar joint, interosseous membrane and DRUJ. The triangular Fibrocartilage complex (TFCC) is the primary structure for intrinsic stability of DRUJ with predominantly radioulnar ligaments. Both superficial and deep radioulnar fibres of TFCC plays role in DRUJ stability. The triangular fibrocartilage complex being an essential stabiliser biomechanically furnishes unrestricted range of motion of forearm. In the tears of radioulnar ligaments, the ulnar sided ligament tears are detected to cause DRUJ instability more common. This article discusses a case of DRUJ instability of both right and left wrists in same patient due to trauma with symptoms at varied time period. The advanced tight rope implant was placed in the wrists to regain the function. This case report compares and discusses the efficacy, recovery and range of motion of two different orientations (straight and oblique) of the advanced tight rope implant in DRUJ instability.